Optical Absorption Spectra and Electronic Properties of Symmetric and Asymmetric Squaraine Dyes for Use in DSSC Solar Cells: DFT and TD-DFT Studies - El-Shishtawy, Reda M. (Int J Mol Sci, 2016)
The electronic absorption spectra, ground-state geometries and electronic structures of symmetric and asymmetric squaraine dyes (SQD1–SQD4) were investigated using density functional theory (DFT) and time-dependent (TD-DFT) density functional theory at the B3LYP/6-311++G** level. The calculated ground-state geometries reveal pronounced conjugation in these dyes. Long-range corrected time dependent density functionals Perdew, Burke and Ernzerhof (PBE, PBE1PBE (PBE0)), and the exchange functional of Tao, Perdew, Staroverov, and Scuseria (TPSSh) with 6-311++G** basis set were employed to examine optical absorption properties. In an extensive comparison between the optical data and DFT benchmark calculations, the BEP functional with 6-311++G** basis set was found to be the most appropriate in describing the electronic absorption spectra. The calculated energy values of lowest unoccupied molecular orbitals (LUMO) were 3.41, 3.19, 3.38 and 3.23 eV for SQD1, SQD2, SQD3, and SQD4, respectively. These values lie above the LUMO energy (−4.26 eV) of the conduction band of TiO(2) nanoparticles indicating possible electron injection from the excited dyes to the conduction band of the TiO(2) in dye-sensitized solar cells (DSSCs). Also, aromaticity computation for these dyes are in good agreement with the data obtained optically and geometrically with SQD4 as the highest aromatic structure. Based on the optimized molecular geometries, relative positions of the frontier orbitals, and the absorption maxima, we propose that these dyes are suitable components of photovoltaic DSSC devices.